ANALYSIS OF DRUG USAGE TOWARD OUT PATIENT IN PANTI NUGROHO HOSPITAL SLEMAN IN OCTOBER 2008 - Charles Aris Sudarmono; Achmad Purnomo; Riswaka Sudjaswadi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Nowadays, the rational drug usage is the main orientation of pharmaceutical service. One of parameter that can be used to measure the rationality of drug usage is by using valuation toward drug usage description, so this research’s done to see the drug usage description toward outpatient in Panti Nugroho Hospital Sleman. This research is descriptive non experimental. The data was taken prospectively with systematic random sampling method. The data taken from the prescription that given for outpatient, patients direct observation that is started from consultation with the doctor in polyclinic until the patients got the drugs, and key drugs (drug of choice) in RSPN Sleman that is analyzed by using WHO drugs usage indicator 1993. The result of this research showed that the average number of drug per encounter is 2,44 R/, the percentage of drugs prescribed by generic name is 27,92%, the percentage of encounters with an antibiotic prescribed is 15,27%, the percentage of encounters with an injection prescribed is 0,33%, and the percentage of drugs prescribed from hospital formulary is 85,05%. However, based on the patients service indicator research result, the result is that the average consultation time is 8 minutes 24 seconds, the average dispensing time is 9 minutes and 56 seconds, the percentage of drugs actually dispensed is 95,89%, the percentage of drugs adequately labeled is 99,66%, and the percentage of patient’s knowledge of correct dosage is 90,00%. From the research result using health facility indicator, it can be seen that in RSPN, there is hospital’s formularium (1), and the percentage of key drugs availability is 100,00%. Keywords : drugs usage description, WHO indicator 1993, Panti Nugroho Hospital Sleman.